What do Canadian universities suggest on their webpages as future career and educational pathways following completion of a kinesiology or exercise science undergraduate program? - Nagpal, Taniya S.; Randhawa, Hanna; Pallister, Rebecca; Fowles, Jonathon R.; O'Brien, Myles W. (Applied Physiology, Nutrition & Metabolism, 2025)
Kinesiology undergraduate programs are multidisciplinary, and graduates may navigate several post-graduate education and career pathways. This study summarized the pathways currently listed online by Canadian undergraduate programs following completion of a kinesiology or "exercise science" degree. An environmental scan was completed by reviewing Canadian undergraduate program (n = 59) webpages and their list of future pathways (n = 845). A content analysis summarized pathways into 46 common categories. The most mentioned pathway was education (n = 60), with coaching, health promotion and physiotherapy next (n = 46–48). Additional pathways included medical, allied health professions, business, and exercise training (n = 24–44). Most listed pathways likely require further training post-graduation.